Assessing labour market slack for monetary policy - Erik Ens; Laurence Savoie-Chabot; Kurt See; Shu Lin Wee (Bank of Canada, 2021)
The large and uneven impact of COVID-19 has emphasized the complexity and diversity of the labour market. This complexity implies that traditional headline measures may be inadequate at providing a comprehensive picture of labour market health. We address this concern in two ways. First, we construct a summary indicator of the labour market and use it to evaluate the level of disagreement between various labour market measures. Our exercise reveals that the COVID-19 shock has heightened the degree of disagreement between different indicators. The unprecedented level of disagreement across individual measures implies that a single measure cannot fully account for differences in labour market slack across various groups, or for the quality of job gains. Second, we propose a comprehensive framework to assess the labour market recovery along three dimensions, all of which capture different elements of slack: overall labour market conditions, labour market inclusiveness and job characteristics. As an example of how to apply this approach, we identify areas of concern in the ongoing recovery of the Canadian labour market.
Keywords: E24; J21; J6; 330; Business fluctuations and cycles; Coronavirus disease (COVID-19); Econometric andstatistical methods; Labour markets; Monetary policy